Enhancing neurocognitive rehabilitation with smart cubes: Design, technology, and programmable games - Jaroslav Vondrak; Vladimir Kasik; Jan Grepl; Terezie Kuboskova; Martin Augustynek; Jan Kubicek; Tereza Benešová; Petr Nilius (Results in Engineering, 2025)
Neurocognitive rehabilitation is essential for restoring cognitive and motor functions in patients with neurological disorders. This study presents a prototype of an innovative smart system based on Tangible User Interface (TUI) technology, specifically designed for neurocognitive rehabilitation. The system comprises a game mat, six smart cubes, and a tablet interface, utilizing infrared (IR) and Bluetooth Low Energy (BLE) communication for accurate spatial detection and wireless interaction. Each cube features an e-ink display, IR LEDs, a microcontroller, and haptic feedback elements. The system enables real-time position and orientation tracking of the cubes and supports adaptive, interactive therapeutic tasks. A series of technical validation experiments were conducted, including detection accuracy under varying optical filter conditions, power consumption analysis, and mechanical durability testing in accordance with IEC 60,601–1. Results demonstrated high detection reliability (up to 98 %) and sufficient structural robustness of the prototype. It is important to emphasize that the primary aim of this study is to present a technical solution in the form of a fully functional prototype; no clinical testing was performed. Clinical evaluation will be addressed in subsequent research phases.